Remapping the European Cultural Memory: The Case of Julia Kristeva's Murder in Byzantium - Rus, Bianca (Atlantis)

(untitled) (Mount Saint Vincent University, 2010)
This article considers Julia Kristeva's novel Murder in Byzantium in the context of some of the most pressing ethical and political dilemmas faced by Europe today, regarding the role of religion and the inclusion of religious references in the Constitution of European Union. It traces Kristeva's remapping of the European tradition, and places feminine creativity at the core of her analysis. I argue that this remapping that revalorizes feminine creativity and sensibility envisions the question of the eternal Europe as an illusion to be endlessly reinvented.